Electronic properties of rutile and anatase TiO2 and their effect on CO2 adsorption: A comparison of first principle approaches. (15th November 2022) - Kovačič, Žan; Likozar, Blaž; Huš, Matej
Highlights: The choice of suitable functional is dependent on the desired property. A high U value or hybrid functional is required for credible electronic properties. Grimme D3 is needed for adsorptions, but not for electronic and optical properties. Activated CO2 displays strong adsorption, bending and charge transfer. Abstract: Photocatalysis is a promising technique for utilizing solar light in chemical synthesis. Among several effective photocatalysts, TiO2 remains the archetypal representative. Using density functional theory calculations, we characterized the geometric, mechanical, electronic and optical properties of rutile and anatase TiO2 . We show that a proper choice of the functional and corrections is of paramount importance. While the geometric and mechanical properties are well reproduced with conventional GGA functionals, electronic properties require at least a Hubbard approach. Despite being revered as superior, hybrid functionals do not necessarily perform better and a prudent choice is required. On the contrary, a lower Hubbard correction is desirable for a proper description of interactions, defects and structures. Lastly, CO2 adsorption was studied on several surfaces. Pristine anatase and rutile surfaces poorly activate CO2, with the exception of rutile (0 0 1), which binds CO2 strongly in a bent form, showing considerable charge transfer and activation.